Le stream comme autonarration - Nathan Ferret (Cahiers de Narratologie)
This article proposes a study of the narrativity specific to the sociotechnical device of live-streaming and its sociological implications. It shows that the streamers of a streaming platform like Twitch share, in the form of streams, multimodal, specular, emergent, shared and interactive self-narratives, supporting identity and monetary commitment of their public. Different from both autobiographies and introspective self-narratives, these streamed self-narratives have the particularity of being based on an inversion of the relationship between plot and character, and of transfiguring the meaning of practices being carried out on screen. By analyzing streaming as a social self-narrative activity, the article allows us to consider it as a device for configuring the narrativity of any form of behavioral expression, and, ultimately, as a part of a capitalist industry of self-narratives.